In Situ DRIFTS Analysis during Hydrogenation of 1-Pentyne and Olefin Purification with Ag Nanoparticles - Cordoba Arroyo, Misael (2023)
The catalytic performance of nanoparticles (NPs) of Ag anchored on different supports was evaluated during the selective hydrogenation of 1-pentyne and the purification of a mixture of 1- pentene/1-pentyne (70/30 vol %). The catalysts were identified: Ag/Al (Ag supported on ɣ-Al2O3), Ag/Al-Mg (Ag supported on ɣ-Al2O3 modified with Mg), Ag/Ca (Ag supported on CaCO3) and Ag/RX3 (Ag supported on activated carbon-type: RX3). Besides, in situ DRIFTS analysis of 1-pentyne adsorption on each supports, catalysts and 1- pentyne hydrogenation were investigated. The results showed that the synthesized catalysts were active and very selective (≥85%) for obtaining the desired product (1-pentene). Different adsorbed species (-CC- and -C=C-) were observed on the supports and catalysts surface using in situ DRIFT analysis, which can be correlated to the activity and high selectivity reached. The role of the supports and electronic properties over Ag improve to H2 dissociative chemisorption during the hydrogenation reactions; promoting the selectivity and the high catalytic performance. Ag/Al and Ag/Al-Mg were the most active catalysts. This was due to the synergism between the active Ag°/Ag+ species and the supports (electronic effects). The results show that Ag/Al and Ag/Al-Mg catalysts have favorable properties and are promising for the alkyne hydrogenation and olefin purification reactions.